2015
DOI: 10.1007/978-3-319-22479-4_14
|View full text |Cite
|
Sign up to set email alerts
|

Inter-organizational Public e-Service Development: Emerging Lessons from an Inside-Out Perspective

Abstract: E-service development has grown to become a daily practice in most public organizations as a means for realizing digital agendas and e-government initiatives on different levels (local, regional, national and transnational governmental levels). Public e-service development is often an inter-organizational (IO) effort with multiple actors and organizations involved in the multi-faceted dimensions of design, development and delivery decisions. Still, there is a lack of research focusing on IO public e-service de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…An inter-organizational project that is set up to deliver seamless digital services for citizens typically involves parties that represent the different government agencies that have a stake in the development and implementation of the digital service [51]. Several authors have identified and reported organizational challenges in inter-organizational collaboration projects, such as lack of resources, development of adequate organizational capabilities, and cultural challenges [67], [68], [69]. In a digital transformation project, these types of organizational challenges may interplay with the challenges of selecting and implementing new digital technologies.…”
Section: Investigating the Interplay Between The Organization The Tec...mentioning
confidence: 99%
See 1 more Smart Citation
“…An inter-organizational project that is set up to deliver seamless digital services for citizens typically involves parties that represent the different government agencies that have a stake in the development and implementation of the digital service [51]. Several authors have identified and reported organizational challenges in inter-organizational collaboration projects, such as lack of resources, development of adequate organizational capabilities, and cultural challenges [67], [68], [69]. In a digital transformation project, these types of organizational challenges may interplay with the challenges of selecting and implementing new digital technologies.…”
Section: Investigating the Interplay Between The Organization The Tec...mentioning
confidence: 99%
“…Furthermore, studies of complexity in IS projects reiterate that selecting the right competencies is highly critical for coping with technological complexity, and should be considered an important task of the project manager [5]. In government digital transformation projects, the ability to select and devote the right resources to the project might be a more critical problem and one that that occurs in current project practice in the public sector, namely the problem of dealing with constrained resources [68], which also impacts the selection of people and competencies for a project.…”
Section: Investigating the Interplay Between The Organization The Tec...mentioning
confidence: 99%
“…Problems that regulatory institutions face when implementing e-government solutions are analyzed by many researchers (Baldwin & Black, 2008Baldwin, Black, & O'Leary, 2014;Blanc, 2013;Blendinger & Michalski, 2018;Carroll & Head, 2010;Cheng, 2014;Choudrie, Zamani, Umeoji, & Emmanuel, 2017;Christiansson, Axelsson, & Melin, 2015;Cledou, Estevez, & Soares Barbosa, 2018;Gil-Garcia, 2012;Hampton, 2005;Juell-Skielse, Lönn, & Päivärinta, 2017;Layfield, 2014;Luna-Reyes, Picazo-Vela, Luna, & Gil-Garcia, 2016;Maegli & Jaag, 2013;Maegli, Jaag, Koller, & Trinkner, 2011;Maume, 2013;Miyazaki, 2018aMiyazaki, , 2018b, who address such aspects as the needs of the society and business enterprises and the challenges and possibilities of meeting those needs, innovations of information systems and technologies, their implementations and impact on increasing e-government᾽s efficiency, regulatory reforms and processes, the best regulatory practices and possibilities to apply them. Researchers pay quite a lot of attention to the analysis of the methods of evaluation of the public sector institutions᾽ efficiency, however, there is not enough of all-encompassing scientific research and solutions regarding the assessment of the regulatory institutions᾽ consolidation while implementing e-government solutions.…”
Section: Introductionmentioning
confidence: 99%
“…The main factors that influence the model of the consolidation of regulatory institutions' activities while implementing e-government solutions are separated into two levels: the regulatory institutions level and the business entities level. The factors of the regulatory institutions level, as well as the factors of the business entities᾽ level fall into four groups according to the spheres of influence of those factors: regulatory processes, expenses, electronic services provision and information and communication means᾽ evaluation levels (Alcaide-Muñoz et al, 2017;Anthopoulos et al, 2016;Baldwin & Black, 2008Baldwin et al, 2014;Benz & Eberlein, 1999;Blockmans et al, 2014;Boer et al, 2016Boer et al, , 2017Cheng, 2014;Choi et al, 2017;Choudrie et al, 2017;Christiansson et al, 2015;González et al, 2009;Hampton, 2005;Janssen & Voort, 2016;Juell-Skielse et al, 2017;Kersbergen & Waarden, 2004;Klievink et al, 2016;Larsson & Grönlund, 2016;Luna-Reyes et al, 2016;Mohan & Parthasarathy, 2016;Mueller, 2003;Navarro-Galera et al, 2016;Scupola & Zanfei, 2016). The first group is the regulatory processes group that encompasses the factors related to the regulatory processes and exercise influence on the regulatory activities.…”
Section: Introductionmentioning
confidence: 99%
“…An important issue for IS project management and egovernment, in practice and research, is to understand how we organize initiatives like this and why some initiatives progress to success while others end in failure (e.g. Heeks and Stanforth, 2007;Melin and Axelsson, 2009;Christiansson et al, 2015).…”
Section: Introductionmentioning
confidence: 99%